Salvation in the New Testament : perspectives on soteriology - Van der Watt, J. G. (Jan Gabriël), 1952- (Supplements to Novum Testamentum, 2005)
Salvation in the New Testament offers an analysis of the soteriological perspectives and language of the different books of the New Testament. Special attention is given to the exciting world of language and imagery used in expressing soteriological ideas.